2003
DOI: 10.1002/cncr.11671
|View full text |Cite
|
Sign up to set email alerts
|

The burdens of cancer therapy

Abstract: Two types of ionic modification approaches (i.e., sulfonation and triethylamination) were applied with the aid of dual‐layer hollow fiber technology in this work to fine tune the pore size and pore size distribution, introduce the electrostatic interaction, and reduce membrane fouling for long‐term high‐performance protein separation. A binary protein mixture comprising bovine serum albumin (BSA) and hemoglobin (Hb) was separated in this work. The sulfonated fiber exhibits an improved BSA/Hb separation factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
165
2
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 528 publications
(174 citation statements)
references
References 48 publications
1
165
2
6
Order By: Relevance
“…18 F-FDG-PET/CT showed promising performance results also in TNBC by both ΔSUV max and ΔTLG measurement (AUC values of 0.86 and 0.88 respectively [41] and overall accuracy of 75% [43]). The potential of ΔTLG as an outcome for 18 F-FDG-PET/CT was confirmed by other research groups, whom showed its correlation with survival [41,44]. In addition, the use of absolute values of SUVmax and SUV peak instead of their difference was also suggested for their better performance in predicting pCR [41].…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…18 F-FDG-PET/CT showed promising performance results also in TNBC by both ΔSUV max and ΔTLG measurement (AUC values of 0.86 and 0.88 respectively [41] and overall accuracy of 75% [43]). The potential of ΔTLG as an outcome for 18 F-FDG-PET/CT was confirmed by other research groups, whom showed its correlation with survival [41,44]. In addition, the use of absolute values of SUVmax and SUV peak instead of their difference was also suggested for their better performance in predicting pCR [41].…”
mentioning
confidence: 78%
“…Early health economic modeling is a method recommended to identify and characterize the uncertainty that is inherent in the early stages of technology development, as it accounts for parameters that are likely to vary and it combines data from different sources [43,44]. The models were designed for two purposes; 1) to inform on go/no-go decisions via early CEAs, i.e.…”
Section: Main Thesis Methodologymentioning
confidence: 99%
See 3 more Smart Citations